Occupational Satisfaction of Physicians: The Impact of Demands and Resources - Pereira, Michelle Morelo; Ferreira, Maria Cristina; Valentini, Felipe (Paidéia (Ribeirão Preto), 2019)
According to the Work Demands and Resources Model, work demands exhaust workers while personal and work resources contribute to their growth. The present study aimed to identify the impact of a work resource (work-family enrichment) and a work demand (overload) on the occupational satisfaction of physicians, as well as the role of a personal resource (harmonious passion for work) as mediator of these relationships. A total of 284 Brazilian physicians participated in the study, of which 52.1% were females. The results of the structural equation modeling showed that work-family enrichment was positively related to occupational satisfaction, while overload was negatively related to this variable. Both relationships were partially mediated by passion for work. It was concluded that the identification and strengthening of the feelings of passion for work of physicians can contribute to the improvement of their occupational well-being, and, consequently, that of their families and customers.